Movement Control System of 3-DOF Quadruped Robot - Amir, Ashadi; Suwardoyo, Untung; Salim K, Ahmad (Program Studi Teknik Elektro Universitas Khairun, 2023)
Robotics technology has been used in various aspects of life to make work easier. In the industrial sector, robots are used to replace human roles in order to produce more effective and efficient work. The use of robots is also carried out in jobs with a high level of risk, one of which is search and rescue (SAR). In its development, the use of robots for SAR requires high flexibility and effectiveness in carrying out movements for finding and extinguishing hotspots as well as rescuing victims. So, in this research, a movement control system will be designed for a legged robot. The robot's design consists of four legs. Each leg of the robot is integrated with three servo motors, so that each leg movement will have three degrees of freedom. Tests are carried out to determine the speed of the robot in various directions of movement by changing the rotation angle of the servo on each leg. The test results show that a legged robot can accelerate at a maximum speed of 0.066 m/s.